2017
DOI: 10.1093/hmg/ddx038
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological analyses of periventricular nodular heterotopia using gyrencephalic mammals

Abstract: Although periventricular nodular heterotopia (PNH) is often found in the cerebral cortex of people with thanatophoric dysplasia (TD), the pathophysiology of PNH in TD is largely unknown. This is mainly because of difficulties in obtaining brain samples of TD patients and a lack of appropriate animal models for analyzing the pathophysiology of PNH in TD. Here we investigate the pathophysiological mechanisms of PNH in the cerebral cortex of TD by utilizing a ferret TD model which we recently developed. To make T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…34) The number of oRG cells was significantly reduced by the dominant-negative FGFR, 34) whereas it was markedly increased by FGF8. 31) These results indicate that FGF signaling plays a pivotal role in producing oRG cells in the OSVZ. Furthermore, our finding raised the possibility that oRG cells mediate cortical folding downstream of FGF signaling.…”
Section: Molecular Investigations Of Cortical Folding Using Ferretsmentioning
confidence: 81%
See 3 more Smart Citations
“…34) The number of oRG cells was significantly reduced by the dominant-negative FGFR, 34) whereas it was markedly increased by FGF8. 31) These results indicate that FGF signaling plays a pivotal role in producing oRG cells in the OSVZ. Furthermore, our finding raised the possibility that oRG cells mediate cortical folding downstream of FGF signaling.…”
Section: Molecular Investigations Of Cortical Folding Using Ferretsmentioning
confidence: 81%
“…Interestingly, our results demonstrated that genetic manipulation of Cdk5 and FGF signaling, which have been reported responsible for human patients with malformation of cortical folds, 23,42,59,60) also produced similar phenotypes in ferrets. 10,31,34) This suggests that similar mechanisms are used to make cortical folds in ferrets and humans. Because marmosets and ferrets have their own unique features, combining transgenic marmosets and electroporated ferrets would facilitate our understanding of the brain of higher mammals.…”
Section: Features Of Ferrets Compared With Marmosetsmentioning
confidence: 96%
See 2 more Smart Citations
“…In situ hybridization was performed as described previously ( Matsumoto et al, 2017 ). Sections prepared from fresh-frozen or fixed tissues were treated with 4% PFA for 10 min, 1 µg/ml proteinase K for 10 min and 0.25% acetic anhydride for 10 min.…”
Section: Methodsmentioning
confidence: 99%